The treatment of domino effects in process hazard analysis. Issue 3 (12th June 2014) - Baybutt, Paul
<x xml:space="preserve">Abstract</x> Domino effects produce hazard scenarios that involve escalating consequences as a chain of linked events propagates throughout and beyond the process where they originate. Such scenarios have been the subject of accident survey studies and quantitative risk analyses but their identification in process hazard analysis (PHA) has received less attention. This article discusses the nature and types of domino effects and a procedure is provided to address them in PHA. The role of separate domino effects studies is described, insights into domino effects that can assist PHA practitioners are provided, and some pitfalls in addressing domino effects are identified. The identification of domino effects in PHA is illustrated using an actual accident that occurred in a refinery. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 220–227, 2015